1990
DOI: 10.1002/j.1537-2197.1990.tb13595.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Sunfleck Sequences and Photoinhibition of Photosynthesis in a Tropical Rain Forest Understory Herb

Abstract: We report the photosynthetic characteristics of a C3 shade plant native to the tropical rain forest understory. It was shown that Elatostema repens Lour. (Hall) f. (Urticaceae) presents a large light adjustment capacity. The effects of several lightfleck sequences on photoinhibition of photosynthesis and carbon gain are analyzed. Photoinhibition is measured both as a decrease in leaf net CO2 uptake in limiting light (shown to be linearly correlated to quantum yield of O2 evolution measured at saturating CO2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In particular, Calathea may be more shade‐adapted than Heliconia . A possible explanation for slightly lower survival in high light is photoinhibition; other understory herbs that were suddenly exposed to large quantities of light have been seen to experience photoinhibition (Gouallec et al, 1990; Lovelock et al, 1994). Photoinhibition is a reduction in the efficiency of photosynthesis resulting from damage to proteins in the photosystems or from the dissipation of excess energy (Krause, 1988), and is often associated with rapid leaf senescence (Lovelock et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Calathea may be more shade‐adapted than Heliconia . A possible explanation for slightly lower survival in high light is photoinhibition; other understory herbs that were suddenly exposed to large quantities of light have been seen to experience photoinhibition (Gouallec et al, 1990; Lovelock et al, 1994). Photoinhibition is a reduction in the efficiency of photosynthesis resulting from damage to proteins in the photosystems or from the dissipation of excess energy (Krause, 1988), and is often associated with rapid leaf senescence (Lovelock et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the growth of six shade-tolerant species was negatively correlated to irradiance. Shadetolerant species may experience photo-inhibition and poor growth in sunflecks lasting 10 minutes or longer (Le Gouallec et al 1990, Krause et al 2007, which can contribute 10-85% of daily light levels (Pearcy 2007). The inverse relationship between low-light survival and magnitude of growth responses to nutrients conflicts with other studies (Denslow et al 1987, Lawrence 2001) that examined only P and inorganic N. Our results suggest that shade-tolerant species have a lower nutrient demand.…”
Section: Discussionmentioning
confidence: 99%
“…Leitsch et aI., 1994). On the other hand, photoinhibition caused by sequences of lightflecks in shade-grown plants of the tropical understory herb Elatostema repens was not reversible in low light during periods up to 45 min (Le Gouallec et al, 1990). Mulkey and Pearcy (1992) demonstrated that long-term (13d) acclimation to gap conditions with daily high light periods increased the ability of leaves to recover from photoinhibition.…”
Section: Iiĩmentioning
confidence: 99%